(untitled) (International Journal of Engineering and Computer Science, 2017)
To develop new materials with desirable electro-magnetic properties those are not currently available to microwave engineers. One unifying theme of the materials should be moderately low loss magnetic materials for microwave applications. Specific properties we have investigated are impedance matched materials, tuned enhanced permeability, reactive impedance surfaces, and negative permeability electromagnetic band-gap materials.